KEBUGARAN JASMANI MAHASISWA D II PGSD PENJAS FIK UNY - F. Suharjana (Jurnal Pendidikan Jasmani Indonesia, 2008)
The need for physical fitness for each individual is different. This difference is usually influenced by the job type of each individual. For post secondary students, physical fitness is important to support learning, attending classes, or doing other activities. That is why every student is expected to have a good fitness in order to support their learning related activities. An individual has a good physical fitness if he or she meets good level according to certain parameter. One of the parameter is Asian Committee on the Standardization of Physical Fitness Test (A.C.S.P.F.T.) for university students which include seven type of test. The results showed that the fitness status of students at D II Elementary School Teacher Education were mostly fitness (98,12%), and only small number of them are not physically fitness (1,88%). In details, their physical fitness could be categorized as follow: very good (26,42%), good (45,28%), medium (26,42%), and low (1,88%). When this description was characterized by gender, the categorization would be as follow: male students were very good (26,19%), good (48,81%), medium (23,81%), and low (1,19%). While female students were very good (27,27%), good (31,82%), medium (36,36%), and low (4,55%). Most of the students body mass index were normal (83,02%) and only a small number of the students were not normal (16,98%). In more details, the body mass index were fat (6,60%), normal (83,02%), lack of nutrition I (8,50%), lack of nutrition II (0,94%) and lack of nutrition (0,94%). Based on the gender, body mass index of male students were (3,57%), normal (86,90%), lack of nutrition I (9,57%), none of them in the category of lack of nutrition II dan III. While body mass index female students were fat (18,18%), normal (68,17%), lack of nutrition I (4,55%), lack of nutrition II (4,55%), and lack of nutrition III (4,55%). Kata Kunci: Kebugaran Jasmani, Indek Masa Tubuh